2020
DOI: 10.17275/per.20.9.7.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Out-of-School Learning Environments in Science Teaching on Motivation for Learning Science

Abstract: This study aims to determine the effect of using out-of-school learning environments in science teaching on motivation for learning science. It is a quasi-experimental study and it has been designed as pre-and posttest experimental study. The study was carried out with seventh grade students enrolled in a secondary school in the city centre of a metropolis of Turkey in 2018 within a period of 20 weeks. There were 28 students in the control group and 28 students in the experiment group. Students' motivation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Effectively, they induce a better understanding of natural sciences concepts (Manzanal, Rodríguez -Barreiro et al, 1999;Prokop et al, 2007;Taş, & Gülen, 2019;Zoldosova & Prokop, 2006), as well as better environmental knowledge, and a more responsible attitude towards nature (Cheeseman & Wright, 2019;Erdoğan, 2011;Karyadi et al, 2018;Martin, 2003). Yildirim (2020) have found that outdoor learning in science teaching had a positive effect on students' attitude, motivation and success. Also, Karyari et al (2018) has suggested that outdoor learning with introduction, exploration and interpretation steps, motivates students to active learning, constructing their understanding through ecosystem observation.…”
Section: The Outdoors Natural Science Lessonmentioning
confidence: 99%
“…Effectively, they induce a better understanding of natural sciences concepts (Manzanal, Rodríguez -Barreiro et al, 1999;Prokop et al, 2007;Taş, & Gülen, 2019;Zoldosova & Prokop, 2006), as well as better environmental knowledge, and a more responsible attitude towards nature (Cheeseman & Wright, 2019;Erdoğan, 2011;Karyadi et al, 2018;Martin, 2003). Yildirim (2020) have found that outdoor learning in science teaching had a positive effect on students' attitude, motivation and success. Also, Karyari et al (2018) has suggested that outdoor learning with introduction, exploration and interpretation steps, motivates students to active learning, constructing their understanding through ecosystem observation.…”
Section: The Outdoors Natural Science Lessonmentioning
confidence: 99%
“…Motivation is defined as a cognitive strength that directs involvement at school. It could be seen from cognitive and affective desire to start and maintain participation in learning activities (Yildirim, 2020;Colquitt, 2011;Wood, 2019). Similarly, motivation covers responsibility, courage to take a risk, sincerity to complete assignments, and have realistic goals.…”
Section: Tablementioning
confidence: 99%
“…It is substantial because it influences students in behaving towards knowledge; hence, students must possess learning motivation to utilize their knowledge (Kostiva & Radoynovska, 2010;Shihusa, 2009). It is a basic recipe for academic success (Hadjichambis, Georgiou, Paraskeva-Hadjichambi, Kyza, & Mappouras, 2016;Yildirim, 2020). It involves internal and external factors that stimulate a person's desire and energy to continue to be interested in and committed to work, roles, or subjects or to make an effort in achieving goals (Jan, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation, as a leader's skill, is this internal unity (Ylmaz et al, 2020) that directs the actions of individuals and gives them meaning. It is a state of excitement (Huang, 2020), both cognition and emotion, physical or intellectual (Yildirim, 2020), which takes individuals to action, in search of the materialization of objectives and goals (Lakerveld et al, 2020;Truong & Le, 2020). The manager's challenge is to accumulate these energies based on the conditions of the workplace (Setiawan, 2020) and other intrinsic and / or extrinsic schemes to the individual.…”
Section: The Steps Of the Managerial Processmentioning
confidence: 99%